Development and validation of spectrophotometric method for quantitative determination of carvedilol in tablets - Maletska, O.; Vasyuk, S.; Zhuk, Y.; Малецька, Олена Романівна; Васюк, Світлана Олександрівна; Жук, Юлія Миколаївна (My University, 2021)
Carvedilol is in a class of medications called beta blockers. It works by relaxing blood vessels and slowing heart rate to improve blood flow and decrease blood pressure.
Keywords: carvedilol; diazonium salts; spectrophotometry; validation